Collaborative smartphone experiments for large audiences with phyphox. (1st September 2022) - Staacks, S; Dorsel, D; Hütz, S; Stallmach, F; Splith, T; Heinke, H; Stampfer, C
Abstract: We present methods to implement collaborative experimentation with smartphone sensors for larger audiences ranging from typical university undergraduate courses of hundreds of students in a lecture hall to world-wide outreaches on the Internet. These methods are based on the app 'phyphox', which is being developed by the authors, and encompass simple data collection via web forms as well as a new network interface for 'phyphox', allowing to collect real-time experiment data from an audience on-site or easy data submission for remote participants. Examples are given with practical considerations derived from first implementations of this method in a lecture hall with 350 undergraduate students as well as a global experiment to determine the Earth's axial tilt with smartphones.